An analytical model to design circumferential clasps for laser-sintered removable partial dentures. Issue 10 (October 2018) - Alsheghri, Ammar A.; Alageel, Omar; Caron, Eric; Ciobanu, Ovidiu; Tamimi, Faleh; Song, Jun
Highlights: A model for rational design of laser-sintered circumferential clasps is proposed. The model adjusts for tooth type, stress, alloy properties, undercut and retention. The model helps to avoid plastic deformation and fatigue failure in clasps. Laser-sintered Co–Cr circumferential clasps are vulnerable to failure in premolars. Abstract: Objective: Clasps of removable partial dentures (RPDs) often suffer from plastic deformation and failure by fatigue; a common complication of RPDs. A new technology for processing metal frameworks for dental prostheses based on laser-sintering, which allows for precise fabrication of clasp geometry, has been recently developed. This study sought to propose a novel method for designing circumferential clasps for laser-sintered RPDs to avoid plastic deformation or fatigue failure. Methods: An analytical model for designing clasps with semicircular cross-sections was derived based on mechanics. The Euler–Bernoulli elastic curved beam theory and Castigliano's energy method were used to relate the stress and undercut with the clasp length, cross-sectional radius, alloy properties, tooth type, and retention force. Finite element analysis (FEA) was conducted on a case study and the resultant tensile stress and undercut were compared with the analytical model predictions. Pull-out experiments were conducted on laser-sintered cobalt–chromium (Co–Cr) dental prostheses to validate the analytical model results. Results: The proposed circumferential clasp design model yields results in good agreement with FEA and experiments. The results indicate that Co–Cr circumferential clasps in molars that are 13 mm long engaging undercuts of 0.25 mm should have a cross-section radius of 1.2 mm to provide a retention of 10 N and to avoid plastic deformation or fatigue failure. However, shorter circumferential clasps such as those in premolars present high stresses and cannot avoid plastic deformation or fatigue failure. Significance: Laser-sintered Co–Cr circumferential clasps in molars are safe, whereas they are susceptible to failure in premolars.